How many, how many, how many - Walton, Rick.; Jabar, Cynthia (Cambridge, Mass. : Candlewick Press, 1993)
The reader counts from one to twelve while guessing the answers to questions about nursery rhymes, names of the seasons, players on a football team, and other basic information.
School Library Journal
Book Links (A.L.A.)
Publisher's Weekly
1.6
K-3
Keywords: Counting -- Juvenile literature; Counting; Questions and answers; Counting; Questions and answers